English for Business (Penerbit Yayasan Prima Agus Teknik, 2021)
English for Business is compiled and intended to provide students of STEKOM University some basic principles in understanding English used in office environment both in writing as well as speaking, so that students will be more prepared to compete in their efforts to look for jobs after finishing their study.This book consists of fourteen (14) units which are divide into threesections: a. Composing paragraphs consisting of the following topics; What is a Paragraph, Two Part of Topic Sentence, Business Letter Format,Understanding Business Letter Types, Application Letter (Cover letter),CV/resume. Business Conversation consisting of the following topics: Polite Requests, Using Business Terms Appropriately, Phone Conversation, and Being a Good Presenter. c. Essay Writing consisting of the following topics: Describing Procedures, Classification, and Interpretation of Data.